2014
DOI: 10.1371/journal.pone.0104563
|View full text |Cite
|
Sign up to set email alerts
|

SILAC-Based Proteomic Profiling of the Human MDA-MB-231 Metastatic Breast Cancer Cell Line in Response to the Two Antitumoral Lactoferrin Isoforms: The Secreted Lactoferrin and the Intracellular Delta-Lactoferrin

Abstract: BackgroundLactoferrins exhibit antitumoral activities either as a secretory lactoferrin or an intracellular delta-lactoferrin isoform. These activities involve processes such as regulation of the cell cycle and apoptosis. While lactoferrin has been shown to exert its function by activating different transduction pathways, delta-lactoferrin has been proven to act as a transcription factor. Like many tumor suppressors, these two proteins are under-expressed in several types of cancer, particularly in breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 77 publications
(124 reference statements)
0
10
0
Order By: Relevance
“…To examine other roles of ␦Lf, in silico analyses of the same promoter sequence, AGCACTTTGG, were performed, and we found expression of the ubiquitin-conjugating enzyme E2 E1 in the cancerous mammary gland MDA-MB-231 cells (Hoedt et al, 2014), suggesting the participation of ␦Lf in the maintenance of cell homeostasis. We identified the same promoter against ␦Lf at −468 bp upstream of the ATG start codon in the RGS3 gene (NG 029512.1) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To examine other roles of ␦Lf, in silico analyses of the same promoter sequence, AGCACTTTGG, were performed, and we found expression of the ubiquitin-conjugating enzyme E2 E1 in the cancerous mammary gland MDA-MB-231 cells (Hoedt et al, 2014), suggesting the participation of ␦Lf in the maintenance of cell homeostasis. We identified the same promoter against ␦Lf at −468 bp upstream of the ATG start codon in the RGS3 gene (NG 029512.1) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence using the MDA-MB-231 metastatic breast cancer cell line that SELENOH is transcriptionally upregulated by the anti-proliferation and anti-migration protein, delta-lactoferrin (Hoedt et al, 2014). These different studies do not clarify how SELENOH may affect metastasis, but redox directed transcription regulated by SELENOH is likely to both influence and be influenced by the stage of cancer cell progression into aggressive metastatic tumors.…”
Section: Other Potential Roles For Selenoproteins In Metastasismentioning
confidence: 99%
“…ΔLf mainly exerts its anti-proliferative and pro-apoptotic activities via its role as a transcription factor. Indeed, ΔLf transactivates different target genes such as Skp1 , DcpS , Bax , SelH , GTF2F2 and UBE2E1 [ 9 , 12 14 ]. A genome-wide pathway analysis and our quantitative proteomic analysis showed that the re-introduction of Lf isoforms in cancerous cells modified essential genes and/or signaling networks responsible mainly for cell survival, apoptosis and RNA processing [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%